Creative Contamination - TERRI SUICO; ANITA DUBROC; ANN MARIE SMITH; LISA HAZLETT; KATHRYN CAPRINO (University of Oklahoma Libraries, 2022)
Four YA adaptations in review: PRIDE by IBI ZOBOI, review by Anita Dubroc FOUL IS FAIR by HANNAH CAPIN, review by Ann Marie Smith SPEAK: THE GRAPHIC NOVEL by LAURIE HALSE ANDERSON and EMILY CARROLL, review by Lisa A. Hazlett THE BABY-SITTERS' CLUB --- REVIEW OF THE NETFLIX ADAPTATION, review by Kathyrn Caprino